Animal NLRs provide structural insights into plant NLR function - Bentham, Adam (Ann Bot, 2017)
Background The plant immune system employs intracellular NLRs (nucleotide binding [NB], leucine-rich repeat [LRR]/nucleotide-binding oligomerization domain [NOD]-like receptors) to detect effector proteins secreted into the plant cell by potential pathogens. Activated plant NLRs trigger a range of immune responses, collectively known as the hypersensitive response (HR), which culminates in death of the infected cell. Plant NLRs show structural and functional resemblance to animal NLRs involved in inflammatory and innate immune responses. Therefore, knowledge of the activation and regulation of animal NLRs can help us understand the mechanism of action of plant NLRs, and vice versa. Scope This review provides an overview of the innate immune pathways in plants and animals, focusing on the available structural and biochemical information available for both plant and animal NLRs. We highlight the gap in knowledge between the animal and plant systems, in particular the lack of structural information for plant NLRs, with crystal structures only available for the N-terminal domains of plant NLRs and an integrated decoy domain, in contrast to the more complete structures available for animal NLRs. We assess the similarities and differences between plant and animal NLRs, and use the structural information on the animal NLR pair NAIP/NLRC4 to derive a plausible model for plant NLR activation. Conclusions Signalling by cooperative assembly formation (SCAF) appears to operate in most innate immunity pathways, including plant and animal NLRs. Our proposed model of plant NLR activation includes three key steps: (1) initially, the NLR exists in an inactive auto-inhibited state; (2) a combination of binding by activating elicitor and ATP leads to a structural rearrangement of the NLR; and (3) signalling occurs through cooperative assembly of the resistosome. Further studies, structural and biochemical in particular, will be required to provide additional evidence for the different features of this model and shed light on the many existing variations, e.g. helper NLRs and NLRs containing integrated decoys.